2020
DOI: 10.3389/fonc.2020.01185
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Fatty Acid Synthase Upregulates Expression of CD36 to Sustain Proliferation of Colorectal Cancer Cells

Abstract: Fatty acid synthase, a key enzyme of de novo lipogenesis, is an attractive therapeutic target in cancer. The novel fatty acid synthase inhibitor, TVB-3664, shows anti-cancer activity in multiple cancers including colorectal cancer; however, it is unclear whether uptake of exogeneous fatty acids can compensate for the effect of fatty acid synthase inhibition. This study demonstrates that inhibition of fatty acid synthase selectively upregulates fatty acid translocase (CD36), a fatty acid transporter, in multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
70
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(85 citation statements)
references
References 52 publications
1
70
2
Order By: Relevance
“…Metabolic reprogramming has been recognized as a hallmark of cancer, wherein changes of glucose and fatty acid metabolic pathways were always involved. CD36 mediated fatty acid uptake and oxidation in tumor cells, and also regulated glucose metabolism in the liver and muscle as reported by ours and others studies 17 , 29 . However, whether CD36 reprograms glucose metabolism of cancer cells is largely unknown.…”
Section: Resultssupporting
confidence: 82%
“…Metabolic reprogramming has been recognized as a hallmark of cancer, wherein changes of glucose and fatty acid metabolic pathways were always involved. CD36 mediated fatty acid uptake and oxidation in tumor cells, and also regulated glucose metabolism in the liver and muscle as reported by ours and others studies 17 , 29 . However, whether CD36 reprograms glucose metabolism of cancer cells is largely unknown.…”
Section: Resultssupporting
confidence: 82%
“…Thus, while this has not been shown directly until recently, the efficacy of FASN inhibitory drugs could be compromised by activating pathways that stimulate the uptake of extracellular FAs and lipids (11,12). Accordingly, a very recent report demonstrated that inhibition of FASN upregulated the lipid receptor CD36 and stimulated the uptake of a lipophilic fluorochrome in colorectal cancer cells (13). In contrast, here we show for the first time that this appears not to be the case in OC.…”
Section: Introductioncontrasting
confidence: 68%
“…FAS and FAO are both important factors that engage in the lipid metabolism and may exert regulation of immune cells [ 125 , 126 ]. Inhibition of FASN has been observed to upregulate expression of CD36, which can compensate for the anti-tumor effects of FASN inhibition [ 199 ]. Therefore, inhibiting CD36 should improve the efficacy of FASN-targeted therapy.…”
Section: Targeting Metabolic Pathways In Combination With Fda-apprmentioning
confidence: 99%